Preparation method of acellular matrix composite gel capable of being cured in situ
By preparing in-situ curable decellular matrix composite gel, using decellular fascia and cancellous bone tissue, the bone defect healing caused by existing osteoinducible materials when biofilm degradation is too fast or autologous repair ability is poor. Poor problems have achieved effective repair and subsequent implant surgery in complex bone defects.
Patent Information
- Application Number
- CN202411575394.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-02-14
AI Technical Summary
When existing bone induction materials degrade too quickly or have poor autologous repair capabilities, they cause insufficient effective connections between bone meals, resulting in poor bone defect healing and difficult to carry out subsequent transplantation work, especially in complex bone defects. Repair is extremely difficult among patients.
Using a preparation method of an in-situ curable decellularized matrix composite gel, the animal fascial tissue and cancellous bone tissue after delipidation are freeze-dried, irradiated and solubilized, combined with nuclear yellow to form an in situ solidified decellular matrix composite gel. The gel is able to cure in situ without relying on the support of a repair membrane, providing bioactivity, support and adhesion properties to promote cell growth and bone tissue regeneration.
This method can significantly improve the effect of alveolar bone defect repair, especially in high-complex bone defects, provide good support capabilities, support subsequent alveolar bone implant surgery, and significantly improve the success rate of repair.
Smart Images

Figure CN119424753A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of medical biomaterials, and in particular relates to a method for preparing an in-situ solidifiable acellular matrix composite gel. Background Art
[0002] There is a window period between implant surgery and alveolar bone defect repair. The optimal implantation period is 3-4 months, which requires the material to have sufficient inductivity; on the other hand, it also requires plasticity and fixation. The existing bone induction material bone powder has no internal connection force, and is mainly shaped and fixed by the outer biofilm. If the biofilm of this material degrades too quickly or the self-repair ability is poor, the biofilm will lose its biomechanical effect and the bone powder will not form a sufficiently effective connection, resulting in bone powder leakage and deformation, which will lead to poor healing of bone defects and difficulty in subsequent implantation. Especially for patients with complex bone defects such as Class 4 alveolar ridge implant sites (the implant site is a horizontal bone defect and the remaining bone volume cannot provide sufficient initial stability) and Class 5 (the implant site is not only accompanied by a horizontal bone defect, but also a vertical bone defect), the existing bone repair materials are extremely difficult to repair. Therefore, it is necessary to provide a new type of material to provide a solution for the repair of complex bone defects. Summary of the invention
[0003] In view of this, the present invention aims to propose a method for preparing an in situ curable acellular matrix composite gel to overcome the deficiencies of the prior art and provide a solution for complex bone defect repair.
[0004] To achieve the above object, the technical solution of the present invention is achieved as follows:
[0005] A method for preparing an in-situ curable decellularized matrix composite gel comprises the following steps:
[0006] 1) Preparation of the first component: animal fascia tissue is subjected to a defatting and decellularizing process, freeze-dried, irradiated, and then freeze-ground into powder; the powder is solubilized and then freeze-dried again;
[0007] 2) Preparation of the second component: freeze-drying the cancellous bone tissue of the animal, grinding it into coarse particles with a mortar, then defatting and decellularizing it, freeze-drying it again, and then freeze-grinding it into powder;
[0008] 3) Adding the first component, the second component and riboflavin into the aqueous solution and uniformly mixing them to obtain an acellular matrix composite gel that can be solidified in situ.
[0009] Preferably, the animal fascia tissue is bovine or porcine fascia tissue; the animal cancellous bone tissue is bovine or porcine cancellous bone tissue.
[0010] Preferably, the degreasing and decellularizing process in step 1) and step 2) comprises the following steps:
[0011] a) Immerse the material to be treated in a peracetic acid solution, stir for 2-4 hours, and then rinse with water for more than 3 times, each time for at least 20 minutes;
[0012] b) immersing the material treated in step a) in a sodium hydroxide solution, stirring for 18-24 hours, neutralizing with a hydrochloric acid solution, and then rinsing with water for more than 3 times, each time for at least 20 minutes;
[0013] c) immersing the material treated in step b) in a sodium dodecyl sulfate solution, stirring for 16-24 hours, and then rinsing with water;
[0014] d) immersing the material treated in step c) in Triton X-100, stirring for 16-24 hours, and then rinsing with water;
[0015] Preferably, after step c) is repeated three times, step d) is performed, and step d) is repeated three times.
[0016] Preferably, in step a), the concentration of the peracetic acid solution is 0.4-0.6% w / v; in step b), the concentration of the sodium hydroxide solution is 0.06-0.08 mol / L, and the concentration of the hydrochloric acid solution is 0.06-0.08 mol / L; in step c), the concentration of the sodium dodecyl sulfate solution is 0.8-1.2% w / v; in step d), the concentration of Triton X-100 is 0.8-1.2% w / v.
[0017] Preferably, in step 1), the solubilizing modification comprises the following steps,
[0018] a) dispersing the powder in a hydrochloric acid solution with a pH of 2-3, adding pepsin and reacting for 18-24 hours;
[0019] b) adjusting the pH of the solution treated in step a) to neutral with sodium hydroxide solution;
[0020] c) dialyzing the solution treated in step b) using a dialysis membrane with a specification of 100 KDa for more than 4 days.
[0021] Preferably, in step a), the concentration of the powder in the solution is 0.1-0.3% w / v; the concentration of pepsin is 0.1-0.5% w / v.
[0022] Preferably, the irradiation source of the irradiation treatment in step 1) is an electron beam, and the irradiation intensity is 15-25 kGy; the grinding temperature of the cryogenic grinding in step 1) and step 2) is -40 to -20°C; the rotation speed of the grinding disc is 500-2000 rpm, more preferably 500-1000 rpm.
[0023] Preferably, in step 3), the concentration of the first component in the solution is 40-50% w / v; the concentration of the second component in the solution is 40-50% w / v; and the concentration ratio of the first component to the second component in the solution is 0.8-1.25; the concentration of riboflavin in the solution is 0.25-0.5% w / v.
[0024] The present invention also provides an in-situ solidification method for the acellular matrix composite gel prepared by the above-mentioned preparation method, using a wavelength of 370nm and a power of 4-8mW / cm 2 UV irradiation for 15-30min.
[0025] The present invention also provides the use of the acellular matrix composite gel prepared by the preparation method described above in the preparation of alveolar bone defect repairing medicine or material.
[0026] The characterization method of the rheological properties of the decellularized matrix composite gel after in-situ curing is as follows: the rheological properties are measured using a TA DHR rotational rheometer with a plate diameter of 25 mm at a gap height of 1 mm and a constant temperature of 25° C. Each measurement is performed at a strain of 1% and a frequency of 1 Hz.
[0027] The viscous modulus of the gel is about 10 Pa to about 500 Pa at 1 Hz, preferably 80-100 Pa. The viscous modulus is measured using a TA DHR rotational rheometer, using a plate diameter of 40 mm at a gap height of 1 mm, at a constant temperature of 25° C. Each measurement is performed at a strain of 0.8% and a frequency of 1 Hz.
[0028] The evaluation method of the alveolar bone defect repair ability of the acellular matrix composite gel is as follows: beagle dogs are used as test subjects, and beagle dogs of moderate size and health are selected. The oral cavity is cleaned and disinfected under appropriate anesthesia conditions. The second canine tooth of the beagle dog is extracted, and an alveolar bone defect model with a diameter of 5 mm is manufactured by drilling and resection. The above-mentioned embodiments and comparative examples are solidified in situ at the site of the bone defect model, and the beagle dogs are given appropriate antibiotics and analgesics after the operation. Bone powder is implanted in the alveolar bone defect site as a control group. The repair of the bone defect site of the beagle dog is evaluated within 2 months after the completion of the operation.
[0029] Compared with the prior art, the method for preparing the in-situ curable decellularized matrix composite gel of the present invention has the following advantages:
[0030] The method for preparing the in situ curable acellular matrix composite gel described in the present invention has in situ gel properties and can be fixed to the alveolar bone defect without relying on the support of a repair membrane. It has significant value for alveolar bone defects, especially highly complex alveolar bone defects.
[0031] The method for preparing the in-situ curable decellular matrix composite gel of the present invention, wherein the decellular matrix fascia material has a natural soft tissue biomimetic fiber scaffold structure and contains rich growth factors; wherein the decellularized cancellous bone has the structural characteristics of bone tissue materials, is conducive to cell growth and induces bone tissue regeneration. Under the synergistic effect of the two materials. The material exhibits excellent biological activity, support and adhesion properties, and the cells around the alveolar bone defect can be effectively induced to the damaged area, and the proliferation phenotype forms an integrated bone-like structure of fiber scaffold-cell matrix-bone tissue, and has good support capacity, which can support subsequent alveolar bone implant surgery. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 This is a hematoxylin-eosin staining image of local tissue after Example 1 was used to repair alveolar bone defects in beagle dogs;
[0033] Figure 2 This is a hematoxylin-eosin staining image of the local tissue after comparative example 1 was applied to the repair of alveolar bone defects in beagle dogs;
[0034] Figure 3 This is the hematoxylin-eosin staining picture of the local tissue of comparative example 6 after being applied to the repair of alveolar bone defect in beagle dogs;
[0035] Figure 4 The Micro-CT results of the local tissues after the first embodiment was applied to the repair of alveolar bone defects in beagle dogs;
[0036] Figure 5 This is the Micro-CT result of the local tissue of comparative example 1 after being applied to the repair of alveolar bone defect in beagle dogs;
[0037] Figure 6 This is the Micro-CT result of the local tissue of comparative example 6 after it was used to repair the alveolar bone defect of beagle dogs. DETAILED DESCRIPTION
[0038] Unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. The test reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the experimental methods, unless otherwise specified, are all conventional methods.
[0039] The present invention will be described in detail below with reference to the embodiments.
[0040] Experiment 1 Preparation method of the first component
[0041] Experiment 1.1
[0042] The porcine fascia tissue was immersed in a 0.4% w / v peracetic acid solution, stirred for 4 hours, and then rinsed with water 4 times, 20 minutes each time. The material was immersed in a 0.08 mol / L sodium hydroxide solution, stirred for 18 hours, neutralized with a 0.08 mol / L hydrochloric acid solution, and then rinsed with water 4 times, 20 minutes each time. The material was immersed in a 0.8% w / v sodium dodecyl sulfate solution, stirred for 24 hours, and then rinsed with water, repeated three times. The material was immersed in 0.8% w / v Triton X-100, stirred for 24 hours, and then rinsed with water, repeated three times. After freeze-drying the material, it was irradiated with an electron beam of 25 kgy, and then freeze-ground into powder. The grinding temperature was -40 ° C and the grinding disc speed was 500 rpm. The above powder was dispersed in a hydrochloric acid solution with a pH of 2 at a concentration of 0.1% w / v, and pepsin with a concentration of 0.1% w / v was added to react for 24 hours. The pH of the solution was adjusted to neutral with sodium hydroxide, and the solution was dialyzed for 4 days with a dialysis membrane with a specification of 100 KDa, and then the solution was freeze-dried twice to obtain the first component.
[0043] Experiment 1.2
[0044] The bovine fascia tissue was immersed in a 0.6% w / v peracetic acid solution, stirred for 2 hours, and then rinsed with water three times, 30 minutes each time. The material was immersed in a 0.06 mol / L sodium hydroxide solution, stirred for 24 hours, neutralized with a 0.06 mol / L hydrochloric acid solution, and then rinsed with water three times, 30 minutes each time. The material was immersed in a 1.2% w / v sodium dodecyl sulfate solution, stirred for 16 hours, and then rinsed with water, repeated three times. The material was immersed in 1.2% w / v Triton X-100, stirred for 16 hours, and then rinsed with water, repeated three times. The material was freeze-dried and irradiated with a 15 kgy electron beam, and then freeze-ground into powder, the grinding temperature was -20 ° C, and the grinding disc speed was 2000 rpm. The above powder was dispersed in a hydrochloric acid solution with a pH of 3 at a concentration of 0.3% w / v, and pepsin with a concentration of 0.5% w / v was added to react for 24 hours. The pH of the solution was adjusted to neutral with sodium hydroxide, and the solution was dialyzed for 4 days with a dialysis membrane with a specification of 100 KDa, and then the solution was freeze-dried twice to obtain the first component.
[0045] Experiment 2 Preparation method of the second component
[0046] Experiment 2.1
[0047] The porcine cancellous bone tissue was freeze-dried and ground into coarse particles. The coarse particles were immersed in a 0.6% w / v peracetic acid solution, stirred for 2 hours, and then rinsed with water three times, 30 minutes each time. The material was immersed in a 0.06 mol / L sodium hydroxide solution, stirred for 24 hours, neutralized with a 0.06 mol / L hydrochloric acid solution, and then rinsed with water three times, 30 minutes each time. The material was immersed in a 1.2% w / v sodium dodecyl sulfate solution, stirred for 16 hours, and then rinsed with water, repeated three times. The material was immersed in 1.2% w / v Triton X-100, stirred for 16 hours, and then rinsed with water, repeated three times. After the material was freeze-dried, it was freeze-ground at a grinding temperature of -40°C and a grinding disc speed of 500 rpm to obtain the second component.
[0048] Experiment 2.2
[0049] The bovine cancellous bone tissue was freeze-dried and ground into coarse particles. The coarse particles were immersed in a 0.4% w / v peracetic acid solution, stirred for 4 hours, and then rinsed with water 4 times, 20 minutes each time. The material was immersed in a 0.08 mol / L sodium hydroxide solution, stirred for 18 hours, neutralized with a 0.08 mol / L hydrochloric acid solution, and then rinsed with water 4 times, 20 minutes each time. The material was immersed in a 0.8% w / v sodium dodecyl sulfate solution, stirred for 24 hours, and then rinsed with water, repeated three times. The material was immersed in 0.8% w / v Triton X-100, stirred for 24 hours, and then rinsed with water, repeated three times. After the material was freeze-dried, it was freeze-ground at a grinding temperature of -40°C and a grinding disc speed of 500 rpm to obtain the second component.
[0050] Example
[0051] This example illustrates the preparation method of the in-situ curable decellularized matrix composite gel and the study of its gel properties.
[0052] The first component, the second component and riboflavin are added into the aqueous solution at the following concentrations and uniformly mixed to obtain an acellular matrix composite gel that can be solidified in situ.
[0053] The above gel was irradiated with ultraviolet light of the following power and wavelength of 370nm for the following time. The composite gel was measured using a TA DHR rotational rheometer with a plate diameter of 25mm at a gap height of 1mm and a constant temperature of 25°C. Each measurement was performed at a strain of 1% and a frequency of 1Hz.
[0054]
[0055] Comparative Example
[0056] The first component, the second component and riboflavin were added to the aqueous solution at the following concentrations and uniformly mixed to obtain an in-situ curable acellular matrix composite gel. The gel was irradiated with ultraviolet light at the following power and wavelength of 370 nm for the following time, and the rheological properties of the gel were studied using a rotational rheometer.
[0057]
[0058] Note: N / A: No gel formed
[0059] It can be seen from Examples 1 to 4 and Comparative Examples 3 to 5 that, when the first component is not added or added at a low concentration, an in-situ curable decellularized matrix hydrogel cannot be formed and has no application value.
[0060] The application of the above-mentioned Example 1, Example 2, Comparative Example 1, Comparative Example 6 and Comparative Example 7 in the repair of alveolar bone defects was examined.
[0061] Beagles were used as test subjects. Moderately sized and healthy beagles were selected. The oral cavity was cleaned and disinfected under appropriate anesthesia conditions. The second canine tooth of the beagle was extracted, and an alveolar bone defect model with a diameter of 5 mm was manufactured by drilling and resection. The above embodiments and comparative examples were in situ cured at the site of the bone defect model, and appropriate antibiotics and analgesics were given to the beagle after the operation. Bone powder was implanted in the alveolar bone defect site as a control group. The repair of the bone defect site of the beagle was evaluated within 3 months after the operation.
[0062]
[0063] The results of the hematoxylin-eosin staining of the local tissues of Example 1, Comparative Example 1 and Comparative Example 6 after being applied to the repair of alveolar bone defects in beagle dogs are as follows: Figure 1-Figure 3 shown.
[0064] The Micro-CT results of the local tissues of Example 1, Comparative Example 1 and Comparative Example 6 after being applied to the repair of alveolar bone defects in beagle dogs are as follows: Figure 4-5 shown.
[0065] It can be seen from the above data that the in situ gelatinizable acellular matrix composite gel described in the present invention, under the action of a suitable formula ratio, exhibits good biological activity, support and adhesion properties. The cells around the alveolar bone defect can be effectively induced to the damaged area, and the proliferation phenotype forms an integrated bone-like structure of fibrous scaffold-cell matrix-bone tissue, and has good supporting capacity, which can support subsequent alveolar bone implant surgery.
[0066] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing an in-situ curable acellular matrix composite gel, characterized in that: The following steps are included: 1) Preparation of the first component: animal fascia tissue is subjected to a defatting and decellularizing process, freeze-dried, irradiated, and then freeze-ground into powder; the powder is solubilized and then freeze-dried again; 2) Preparation of the second component: freeze-drying the cancellous bone tissue of the animal, grinding it into coarse particles with a mortar, then defatting and decellularizing it, freeze-drying it again, and then freeze-grinding it into powder; 3) Adding the first component, the second component and riboflavin into the aqueous solution and uniformly mixing them to obtain an acellular matrix composite gel that can be solidified in situ.
2. The method for preparing the in-situ curable acellular matrix composite gel according to claim 1, characterized in that: The animal fascia tissue is the fascia tissue of cattle or pigs; the animal cancellous bone tissue is the cancellous bone tissue of cattle or pigs.
3. The method for preparing the in-situ curable acellular matrix composite gel according to claim 1, characterized in that: The degreasing and decellularizing process in step 1) and step 2) comprises the following steps: a) Immerse the material to be treated in a peracetic acid solution, stir for 2-4 hours, and then rinse with water for more than 3 times, each time for at least 20 minutes; b) immersing the material treated in step a) in a sodium hydroxide solution, stirring for 18-24 hours, neutralizing with a hydrochloric acid solution, and then rinsing with water for more than 3 times, each time for at least 20 minutes; c) immersing the material treated in step b) in a sodium dodecyl sulfate solution, stirring for 16-24 hours, and then rinsing with water; d) immersing the material treated in step c) in Triton X-100, stirring for 16-24 hours, and then rinsing with water; Preferably, after step c) is repeated three times, step d) is performed, and step d) is repeated three times.
4. The method for preparing the in-situ curable acellular matrix composite gel according to claim 3, characterized in that: In step a), the concentration of the peracetic acid solution is 0.4-0.6% w / v; in step b), the concentration of the sodium hydroxide solution is 0.06-0.08 mol / L, and the concentration of the hydrochloric acid solution is 0.06-0.08 mol / L; in step c), the concentration of the sodium dodecyl sulfate solution is 0.8-1.2% w / v; in step d), the concentration of Triton X-100 is 0.8-1.2% w / v.
5. The method for preparing the in-situ curable acellular matrix composite gel according to claim 1, characterized in that: In step 1), the solubilizing modification comprises the following steps, a) dispersing the powder in a hydrochloric acid solution with a pH of 2-3, adding pepsin and reacting for 18-24 hours; b) adjusting the pH of the solution treated in step a) to neutral with sodium hydroxide solution; c) dialyzing the solution treated in step b) using a dialysis membrane with a specification of 100 KDa for more than 4 days.
6. The method for preparing the in-situ curable acellular matrix composite gel according to claim 5, characterized in that: In step a), the concentration of the powder in the solution is 0.1-0.3% w / v; the concentration of pepsin is 0.1-0.5% w / v.
7. The method for preparing the in-situ curable acellular matrix composite gel according to claim 1, characterized in that: In the irradiation treatment in step 1), the irradiation source is an electron beam, and the irradiation intensity is 15-25 kGy; in the cryo-grinding in step 1) and step 2), the grinding temperature is -40 to -20°C; the rotation speed of the grinding disc is 500-2000 rpm, more preferably 500-1000 rpm.
8. The method for preparing the in-situ curable acellular matrix composite gel according to claim 1, characterized in that: In step 3), the concentration of the first component in the solution is 40-50% w / v; The concentration of the second component in the solution is 40-50% w / v; and the concentration ratio of the first component to the second component in the solution is 0.8-1.25; the concentration of riboflavin in the solution is 0.25-0.5% w / v.
9. The in-situ solidification method of the acellular matrix composite gel prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The wavelength is 370nm and the power is 4-8mW / cm 2 UV irradiation for 15-30min.
10. Use of the acellular matrix composite gel prepared by the preparation method according to any one of claims 1 to 8 in preparing drugs or materials for repairing alveolar bone defects.